Transforming food systems in Maritime Southeast Asia and Pacific Small Island Developing States to support food security and sustainable healthy diets - Chiew, Foan Chin; Ee, Von Goh; Andrew C. Clarke; Li, Michelle Ern Ang; Pau, Loke Show; Christina V. Supramaniam; Asgar Ali; Susan Azam-Ali; Richard Beyer; Alvin Culaba; Heli Siti Halimatul Munawaroh; Kinaai Kairo; et al. (Frontiers Media S.A., 2024)
Food is one of the basic necessities for human life. Nutritious food is essential for human health and helps oneself live up to our best potential as productive members of society. In spite of this, 3 billion people are estimated to have limited access to nutrient-rich food, and there are 768 million undernourished people in the globe today. There are still concerns with food systems and food security, despite the fast economic transformation of low-and middle-income nations in Maritime Southeast Asia and Oceania over the past 10 years. These issues include dwindling agricultural land, deforestation, ineffective food supply networks, environmental degradation, changing and unhealthy diets, non-communicable diseases, disappearing cultural legacy, and ineffective policies. These problems are exacerbated by climate change, natural hazards, and pandemic shocks. This review explores the perspectives of food systems that relates to all the elements and activities in transforming agri-food industry. In this paper, we discuss the challenges and solutions to transforming food systems in this region to achieve a sustainable and healthy diet for all, with the perspective of bringing the region closer toward the UN sustainable development goals. This paper is an outcome of the deliberations that took place during the Food Security in Small Islands and Developing States workshop in 2020. It also includes insights from subsequent expert group sessions that focused on the following topics: Agriculture and Food Systems; Nutrition, Health, and Culture; Innovations and Digitalization in Food Systems; as well as Policies Coordination and Future Shocks.